2010
DOI: 10.1002/smll.200902370
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chemical Modification of Graphene Surfaces: Distinction Between Single‐ and Bilayer Graphene

Abstract: Graphene modifications with oxygen or hydrogen are well known in contrast to carbon attachment to the graphene lattice. The chemical modification of graphene sheets with aromatic diazonium ions (carbon attachment) is analyzed by confocal Raman spectroscopy. The temporal and spatial evolution of surface-adsorbed species allows accurate tracking of the chemical reaction and identification of intermediates. The controlled transformation of sp(2) to sp(3) carbon proceeds in two separate steps. The presented deriva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
265
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(291 citation statements)
references
References 32 publications
22
265
3
1
Order By: Relevance
“…8d), [233] providing new possibilities to systematically study the electrochemical properties of graphene. The correlation indicates that the electrochemical activity first increases with the defect density (in line with earlier reported higher reactivity for covalent derivatization [122,234] ), and then decreases when 'defective' graphene sheet losses its structure integrity (i.e., presumably when the aromaticity of graphene is totally lost). As a perspective, a GFET biosensor can in principle be combined with a GEC biosensor we described here in a same device, and thus providing a fully complementary sensing platform to study both the electrostatic charge of the biomolecules but also the charge transfer during redox reaction at the graphene surface.…”
Section: Graphene-based Electrochemical (Gec) Biosensorssupporting
confidence: 85%
See 1 more Smart Citation
“…8d), [233] providing new possibilities to systematically study the electrochemical properties of graphene. The correlation indicates that the electrochemical activity first increases with the defect density (in line with earlier reported higher reactivity for covalent derivatization [122,234] ), and then decreases when 'defective' graphene sheet losses its structure integrity (i.e., presumably when the aromaticity of graphene is totally lost). As a perspective, a GFET biosensor can in principle be combined with a GEC biosensor we described here in a same device, and thus providing a fully complementary sensing platform to study both the electrostatic charge of the biomolecules but also the charge transfer during redox reaction at the graphene surface.…”
Section: Graphene-based Electrochemical (Gec) Biosensorssupporting
confidence: 85%
“…II). The reaction efficiency depends on several parameters: the number of graphene layers, [122] the electrostatic environment, [123] and the defect density on the graphene surface. [124] A previous study exploited the graphene reactivity, induced by electrostatic charge doping on different substrates using reactivity imprint lithography (RIL).…”
Section: Covalent Functionalizationsmentioning
confidence: 99%
“…However, a systematic increased doping level for bilayer graphene cannot be excluded, since it could be in agreement with recent experimental results on chemically functionalized graphene where it has been found that adsorbates bind differently to single-and bilayer graphene. 42 From Fig. 5(b), we can also notice that at the estimated p-doping values (indicated by the vertical line), the small charging n = 1.4 ×10 11 cm −2 induced upon contact with the biased AFM tip only leads to a minor modification of the work functions, i.e., of V (2−1) dc as observed in our experiment and mentioned above.…”
Section: A Layer Dependent Work Function Differencessupporting
confidence: 77%
“…17 We note that under identical conditions HOPG samples did not give the same results and it appears that the product structure responsible for the Raman features described above are specific to graphene; in fact, even bilayer graphene (2-LG) samples behave differently. 20,21 In the bilayer graphene sample (Figure 1c), the 2D band can be fitted with four Lorentzians (Figure 1c inset). The D, D*, D + D* bands in the product are broad and weak although they are observed at the same frequency as in the 1-LG samples ( Figure 1d).…”
mentioning
confidence: 99%